Determine Nasal Carriage of Methicillin Resistant Staphylococcus aureus MRSA in Young Adult College Student - N. Saeed, Ebtihal; I.Omer Al-Deen, Hanan; A. Merdaw, Maysoon (Iraqi Journal of Pharmaceutical Sciences, 2017)
Present study was carried out to find prevalence of MRSA in healthy individual of second stage students, college of pharmacy/Baghdad University. A total of 74 student selected between age 18-23 years old were included in this study, nasal swabs collected and subjected to many diagnostic standard bacteriological identification methods. Culture, colonial morphology, Gram stain, mannitol fermentation, coagulase ,gelatinasetest, DNAase, MR/VP and antimicrobial susceptibility test was performed on tryptic soy agar by modified Kirby-Bauer muller hinton disc diffusion method and the result show that out of 74 nasal swabs,67(90.5%) were MRSA positive isolates, 21(31.4%) of them were mannitol ferment and 46(68.6%) non mannitol fermenter, among these isolates 33(44.6%)male and 41(55.4%) female, there was no significant sex difference in the prevalence of Staph. aureus, while show decrease in prevalence with age group,(54%),(27%),(9.5%) alternatively, MRSA positive isolates indicated relatively high rate of resistance to antibiotics, so to vancomycin 3(4.5%),ciprofloxacin 4(6%) , tetracyclin 9(13.5%) ,gentamycin 6(9%), erythromycin 15(22.5%) and keflex 20(30%). This study show a high prevalence of MRSA carriage in young adult college student (healthy people) that indicating the spread of MRSA in the community which consider high risk of spreading infections also we isolate non mannitol fermenter (MRSA) Staph. aureus that need further moleculer analysis to prove it. Keywords: Staphylococcus aureus , MRSA, Modified Kirby-Baur methods.